C++20 for programmers - Deitel, Paul J.; Deitel, Harvey M., 1945- (Deitel developer series., 2021)
In C++20 for programmers, the Deitels bring their proven Live Code approach to teaching today's powerful new version of the C++ language. Like all Deitel Developer titles, they teach the best way possible: via hundreds of complete example C++ programs, with thousands of lines of downloadable C++ source code. C++20 for Programmers C++20 for Programmers is an introductory-through-intermediate-level, tutorial presentation of computer programming in the latest version (C++20) of the C++ programming language, which is popular for developing systems software, embedded systems programming, operating systems, real-time systems, communications systems and other high-performance computer applications. Ideal for anyone who's worked with at least one programming language before, C++20 for Programmers utilizes a proven "early objects" approach, emphasizing program clarity, software reuse, and component-oriented software construction. In addition to the core language, it will help you take advantage of the newest standard libraries and the newest language extensions.